Your student research project - Luck, Martin (Hampshire Gower, 1999)
This text offers practical advice on how to cope with a project, with chapters covering motivation and skills, choosing a topic, planning research, reading the literature, making progress and writing it up. The text emphasizes using skills gained in the world beyond university.